Incorporation of fast dissolving glucose porogens and poly(lactic-co-glycolic acid) microparticles within calcium phosphate cements for bone tissue regeneration. (15th September 2018) - Smith, Brandon T.; Lu, Alexander; Watson, Emma; Santoro, Marco; Melchiorri, Anthony J.; Grosfeld, Eline C.; van den Beucken, Jeroen J.J.P.; Jansen, John A.; Scott, David W.; Fisher, John P.; Mikos, Antonios G.
Graphical abstract: Abstract: This study investigated the effects of incorporating glucose microparticles (GMPs) and poly(lactic-co-glycolic acid) microparticles (PLGA MPs) within a calcium phosphate cement on the cement's handling, physicochemical properties, and the respective pore formation. Composites were fabricated with two different weight fractions of GMPs (10 and 20 wt%) and two different weight fractions of PLGA MPs (10 and 20 wt%). Samples were assayed for porosity, pore morphology, and compressive mechanical properties. An in vitro degradation study was also conducted. Samples were exposed to a physiological solution for 3 days, 4 wks, and 8 wks in order to understand how the inclusion of GMPs and PLGA MPs affects the composite's porosity and mass loss over time. GMPs and PLGA MPs were both successfully incorporated within the composites and all formulations showed an initial setting time that is appropriate for clinical applications. Through a main effects analysis, we observed that the incorporation of GMPs had a significant effect on the overall porosity, mean pore size, mode pore size, and in vitro degradation rate of PLGA MPs as early as after 3 days ( p < 0.05). After 4 wks and 8 wks, these same properties were affected by the inclusion of both types of MPs ( p < 0.05). Advanced polymer chromatography confirmed that the degradation of PLGA MPs coincided with an increase in composite porosity, mean pore size, and mode pore size. Finally, it was observed that the inclusion of GMPs slowed the degradation of PLGA MPs in vitro and reduced the solution acidity due to PLGA degradation products. Our results suggest that the dual inclusion of GMPs and PLGA MPs is a valuable approach for the generation of early macropores, while also mitigating the effect of acidic degradation products from PLGA MPs on their degradation kinetics. Statement of significance: A multitude of strategies and techniques have been investigated for the introduction of macropores with calcium phosphate cements (CPC). However, many of these strategies take several weeks to months to generate a maximal porosity or the degradation products of the porogen can trigger a localized inflammatory response in vivo . As such, it was hypothesized that the fast dissolution of glucose microparticles (GMPs) in a CPC composite also incorporating poly(lactic-co-glycolic acid) (PLGA) microparticles (MPs) will create an initial macroporosity and increase the surface area within the CPC, thus enhancing the diffusion of PLGA degradation products and preventing a significant decrease in pH. Furthermore, as PLGA degradation occurs over several weeks to months, additional macroporosity will be generated at later time points within CPCs. The results offer a new method for generating macroporosity in a multimodal fashion that also mitigates the effects of acidic degradation products.